Between theater & anthropology - Schechner, Richard, 1934- (Philadelphia : University of Pennsylvania Press, 1985)
For over two decades Richard Schechner has written about the theater in a manner which ignores the dreary convention of drama as literature and which instead draws attention to the physical fact of live performance. In his recent book, Between Theater and Anthropology, Schechner considers live events or aspects of live events which fall outside common Euro-American definitions of dramatic performance and theater. He broadens the idea of 'performance' to include a wide range of social, ritual, and media activities: East Indian ritual dancing, trance-inducing spiritual song, stories on the Six O'clock News, S/M parlors and sideshows, and numerous other paratheatrical events - scripted and un-scripted, ritual and aesthetic, domestic and exotic. The seven essays included in Between Theater and Anthropology do not build upon each other in a progressive fashion: instead they individually explore unorthodox performance modes proposed in the introductory chapter. This first chapter illuminates 'Points of Contact' between the studies of theater and anthropology. Theater people can help anthropologists identify what to look for in a training or performance situation; and anthropologists can help theater people see performances within the context of specific social systems.
Points of contact between anthropological and theatrical thought -- Restoration of behavior -- Performers and spectators transported and transformed -- Ramlila of Ramnagar -- Performer training interculturally -- Playing with Genet's Balcony: looking back on a 1979/1980 production -- News, sex, and performance theory.
Includes bibliographical references (pages 325-332) and index.
Print version record.
JSTOR
Keywords: Theater -- Anthropological aspects; Rites and ceremonies; Performing arts; Theater; Anthropology; Anthropology; Théâtre.; Anthropologie; Rites et cérémonies.; Arts du spectacle; Théâtre -- Aspect anthropologique; theater (discipline); anthropology; performing arts (discipline); 24.02 theory and aesthetics of theatre; 73.62 art (ethnology); DRAMA -- General; Theater; Anthropology; Performing arts; Rites and ceremonies; Theater -- Anthropological aspects; Theater; Anthropology; Rituals; Ceremonies; TEATRO (ASPECTOS ANTROPOLÓGICOS); PERFORMANCE (ASPECTOS ANTROPOLÓGICOS); Esthétique de la réception.; Arts du spectacle -- Anthropologie; Rites et cérémonies.; Théâtre -- Anthropologie; Spectator; Production; United States history; Sex; News; Intercultural; Training; Transformation; Performers; Behavior; Contact; Anthropology; Mexico; General reference